Novel metal complexes of 3‐acetylcoumarin‐2‐hydrazinobenzothiazole Schiff base: Design, structural characterizations, DNA binding, DFT calculations, molecular docking and biological studies. (10th March 2020) - Elsayed, Shadia A.; El‐Gharabawy, Hoda M.; Butler, Ian S.; Atlam, Faten M.
Abstract : Five new Cu (II), Zn (II), Pd (II), Ru (III) and Ag(I) complexes, derived from the 3‐acetylcoumarin‐2‐hydrazinobenzothiazole Schiff base (Hachbt), have been synthesized and characterized. The structures were established with the aid of elemental analyses (C, H, N), FT‐IR, 1 H‐NMR, ESR, UV–visible and ESI‐mass spectra. The complexes were also investigated by magnetic susceptibility, thermal gravimetric analysis (TG‐DTA) and cyclic voltammetry measurements. The results suggest that the Schiff base ligand behaves in two different ways: neutral mono/bidentate or mono‐negative bi/tridentate. The calf thymus DNA (CT DNA) binding affinities of Hachbt and its complexes have been examined by UV–visible spectroscopy. The antifungal activity of the compounds was also screened against two fungal species of wood‐decay basidiomycetes using the agar dilution method. Different complexes caused a reduction in the fungal colony diameters at a media concentration of 100 μg/ml. The best antifungal activity was observed for the Pd (II) and Ag(I) complexes with a 60% and 79% reduction, respectively. The effect of the complexes on the ability of the same fungi to decolorize poly‐R dye on agar plates was also tested. All of the complexes showed an enhanced effect on the decolorization ability and the Cu (II) and Ru (III) complexes exhibited the strongest effect at a media concentration of 5 μg/ml. Theoretical studies were performed for all the complexes using the DFT/B3LYP/6–31 + g(d) basis set for calculations on the ligand atoms and LAN2DZ for the Pd (II) complex. The optimized geometries were found to be in a good agreement with the proposed structures. The molecular docking calculations show that the binding affinity of the Pd (II) complex is −309.170‐309.2 kcal/mol, which suggests complexation with the DNA minor groove. Abstract : Novel metal complexes of 3‐acetylcoumarin‐2‐ hydrazinobenzothiazole Schiffbase: Design, structural characterizations, DNA binding, DFT calculations, molecular docking and biologicalstudiesShadia A. Elsayed, Hoda M. El‐Gharabawy, and Ian S. Butler, Faten M. Atlam*Five new Cu(II), Zn(II), Pd(II), Ru(III) and Ag(I) complexes, derived from the3‐acetylcoumarin‐2‐hydrazinobenzothiazole Schiff base (Hachbt).The calf thymus DNA (CT DNA) bindingaffinities of Hachbt and its complexes have been examined by UV‐visible spectroscopy.The optimizedgeometries were found to be in a good agreement with the proposed structures. The molecular dockingcalculations show that the binding affinity of the Pd(II) complex is ‐309.170‐309.2 kcal/mol, which suggestscomplexation with the DNA minor groove.inert graphical abstract accordingly.